Image focus measure based on polynomial coefficients and spectral radius. Issue 1 (December 2015) - Gaidhane, Vilas; Hote, Yogesh; Singh, Vijander
Abstract In this paper, a new measure of image focus based on the statistical properties of polynomial coefficients and spectral radius is proposed. Spectral radius captures the dominant features and represents the important dynamics of an image. It is shown that the proposed focus measure is monotonic and unimodal with respect to the degree of defocusation, noise and blurring effects. Moreover, it is sufficiently invariant to contrast changes occur due to the variations in intensities of illumination. The noise studies show that the proposed focus measure is robust under the different noisy and blurring conditions. The performance of proposed focus measure is gauged by comparing with the existing image focus measures. Experimental results using synthetic as well as real-time images with known and unknown distortion conditions show the wider working capability and higher prediction consistency of the proposed focus measure. Moreover, the performance of the proposed approach is validated with most popular five image quality databases: TID2008, LIVE, CSIQ, IVC and Cornell-A57. Experimentation on the databases shows that the proposed metric provides the comparatively higher correlation with ideal mean observer score than the existing metrics.